(untitled) (Journal of Applied Learning and Teaching, 2025)
Despite the ubiquitous use of generative artificial intelligence (GenAI) in education, there is an urgent need to explore its potential to co-create culturally relevant assessment material for learners. This study aims to fill this void by exploring how GenAI can be used to co-create material that is sensitive to learners from diverse cultural backgrounds while being cognisant of inclusivity and equitable assessment opportunities. Through a synthesis of literature, the culturally relevant pedagogy framework, and assessment materials co-created by GenAI, the study seeks to empower pre-service teachers, practitioners, teacher-educators in higher education institutions and policymakers to integrate GenAI-driven assessment in their teaching. The key findings indicate a positive correlation between GenAI integration and enhanced cultural relevance in assessment materials co-creation. This innovative, pedagogical curriculum design case contributes to the discourse on GenAI in culturally relevant assessment practices and advocates for a paradigm shift that emphasises cultural responsiveness and inclusivity.